An unusual case of hematuria in a French family returning from Corsica. (February 2015) - Brunet, Julie; Pfaff, Alexander W.; Hansmann, Yves; Gregorowicz, Guillaume; Pesson, Bernard; Abou-Bacar, Ahmed; Candolfi, Ermanno
Highlights: An unusual case of hematuria in France. Local transmission of S. haematobium in Corsica (France) Bulinus truncatus, the intermediate snail hosts, have been described in Europe. S. haematobium could potentially spread to Europe. Urinary schistomiasis diagnosis should be considered in suspicious haematuria cases. Summary: Urinary schistosomiasis caused by Schistosoma haematobium worms is endemic to tropical regions where it is the most common cause of hematuria. However, the intermediate snail hosts, Bulinus truncatus, have been described in Portugal, Spain, Sardinia, and Corsica. S. haematobium has long remained exotic to Europe, however, an outbreak of urinary schistosomiasis in Corsica started in 2011 with B. truncatus as the primary intermediate host. We describe the case of a 12-year-old French boy presenting hematuria and dysuria who was diagnosed with urinary schistosomiasis. Urine examination confirmed the presence of viable parasitic ova. He also had a positive serology. Since there was no history of travel to a schistosomiasis endemic region, the probable area of contamination was identified as the south of Corsica where the family had spent their summer holidays 7 months earlier. Two other family members had a positive serology without ova excretion in urine. The patients were treated with praziquantel. In light of these recent locally acquired cases in France, schistosomiasis should be considered in the differential diagnosis of hematuria, especially in patients who have recently visited Corsica.